Macroinvertebrados bentônicos bioindicadores de condições de referência - Isabela Sobrinho Martins (2016)
Areas with minimal anthropogenic influences are called "reference sites" and represent the best possible ecological status available in a region. The objective of this study was to define and characterize streams in reference conditions and also assess streams from different regions of the same watershed. The question that guided this study was: Arestreams in reference conditions located in different regions of the same watershed are distinguished in their physical and biological characteristics? The study hypothesis was that streams in reference conditions located in a same region more homogeneous to eachother than to streams located in different areas. The 29 streams in reference conditions located in three distinct regions in the Araguari river basin, MG, were characterized by physical habitats, physical and chemical water characteristics and benthic macroinvertebrates as biological indicators. The characterization of streams in referenceconditions in Araguari River basin indicates that there are significant differences between the three regions in regards to habitat characteristics, physical and chemical water characteristics and taxonomic composition of benthic communities. Richness andtaxonomic composition of benthic macroinvertebrate communities were negatively influenced by the slope and positively by the presence of leaf deposits. For the definition of reference sites, regional characteristics should be taken into consideration because the watershed is not a homogeneous unit due to differences in environmental structure, geology, soil, physical habitats and biological composition.